2019
DOI: 10.1002/ajmg.a.61184
|View full text |Cite
|
Sign up to set email alerts
|

Continuum of phenotypes in hereditary motor and sensory neuropathy with proximal predominance and Charcot–Marie–Tooth patients with TFG mutation

Abstract: Charcot-Marie-Tooth (CMT) is a common neuropathy, and hereditary motor and sensory neuropathy with proximal predominance (HMSN-P) is a recently described rare neuromuscular disease. Although many genes have been implicated for CMT, TFG is the only known HMSN-P-causing gene. Within the framework of diagnostic criteria, clinical variation is evident among CMT-diagnosed and also HMSN-P-diagnosed individuals. Mutations that cause p.(Pro285Leu) and p.(Gly269Val) in TFG were earlier reported as cause of HMSN-P in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It seems that the clinical features of our patients had an overlap between CMT2 and HMSN‐P. Actually, patients carrying TFG p.Gly269Val have been reported in patients with either CMT2 or HMSN‐P (Khani, Shamshiri, Alavi, Nafissi, & Elahi, 2016; Khani et al., 2019; Tsai et al., 2014) This implied a continuum of phenotypes in HMSN‐P and CMT patients with TFG mutations (Fabrizi et al., 2020; Khani et al., 2019).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…It seems that the clinical features of our patients had an overlap between CMT2 and HMSN‐P. Actually, patients carrying TFG p.Gly269Val have been reported in patients with either CMT2 or HMSN‐P (Khani, Shamshiri, Alavi, Nafissi, & Elahi, 2016; Khani et al., 2019; Tsai et al., 2014) This implied a continuum of phenotypes in HMSN‐P and CMT patients with TFG mutations (Fabrizi et al., 2020; Khani et al., 2019).…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies revealed that TFG mutations were associated with hereditary motor and sensory neuropathy with proximal dominant involvement (HMSN-P), (Alavi, Shamshiri, & Nafissi, 2015;Ishiura, Sako, & Yoshida, 2012) which is characterized by predominantly proximal muscle weakness and atrophy, widespread fasciculations, cramps, and late-onset distal sensory deficit. It seems that the clinical features of our patients had an overlap between CMT2 and HMSN-P. Actually, patients carrying TFG p.Gly269Val have been reported in patients with either CMT2 or HMSN-P (Khani, Shamshiri, Alavi, Nafissi, & Elahi, 2016;Khani et al, 2019;Tsai et al, 2014) This implied a continuum of phenotypes in HMSN-P and CMT patients with TFG mutations (Fabrizi et al, 2020;Khani et al, 2019).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…YIF1B causes a progressive encephalopathy with movement disorders, microcephaly, and epilepsy with Golgi and primary cilium alterations [65]. (ii) Late-onset presentations (from late childhood to adulthood) are related with motor dysfunctions such spastic paraparesis (i.e., TANGO2, SLC33A1 defects), and Charcot-Marie-Tooth (CMT) disease (i.e., TFG, CNPNY3 defects) [66].…”
Section: Clinical Presentations Of Traffic Disordersmentioning
confidence: 99%
“…This possibility is negated by observation of sensory indications in the MND‐227 patients and the absence of sensory indications in all forms of SMA. All in all, the clinical and genetic findings pertaining to MND‐227 patients are yet another indication of the complexities and overlaps amongst various neurological diseases [7, 50–53]. Here, these issues are imperfectly resolved by designating the name “non‐Kennedy SBMA” to the disease MND‐227.…”
Section: Discussionmentioning
confidence: 99%